DNA Ploidy is Stronger Than Lymph Node Metastasis as Prognostic Factor in Cervical Carcinoma: 10-Year Results of a Prospective Study. Issue 4 (1st April 2011) - Susini, Tommaso; Olivieri, Simone; Molino, Cecilia; Amunni, Gianni; Rapi, Stefano; Taddei, Gianluigi; Scarselli, Gianfranco
Abstract : Introduction: To improve the outcome of patients with cervical cancer, a more accurate prognostic assessment is essential. The aim of this study was to evaluate the role of tumor DNA ploidy as an independent prognostic factor in cervical carcinoma. Furthermore, we investigated whether the presence of lymph node metastasis may have a different clinical impact according to ploidy status. Methods: In a long-term prospective study, DNA ploidy was evaluated by flow cytometry from fresh tumor samples from 136 patients with cervical cancer who underwent surgery. Ploidy, lymph node metastasis, and other classical parameters were analyzed in relation to the length of disease-specific survival. Treatment modalities did not differ between patients with diploid tumors and patients with aneuploid tumors. Results: DNA aneuploidy was found in 52 patients (38.2%). Patients with DNA-aneuploid tumors had a significantly reduced disease-specific survival ( P = 0.003). Overall, the 10-year survival probability was 54% for patients with DNA-aneuploid tumors and 80% for patients with DNA-diploid tumors. Among 64 patients with International Federation of Gynecologists and Obstetricians stage I disease, the 10-year survival rates were 38.7% for the patients with DNA-aneuploid tumors and 86.3% for those with DNA-diploid tumors ( P = 0.003). Overall, diploid tumors with lymph node metastasis did significantly better than aneuploid tumors with lymph node metastasis ( P = 0.05). Among the patients with International Federation of Gynecologists and Obstetricians stage I disease, there was a highly significant difference between patients with diploid node-positive tumors and patients with aneuploid node-positive tumors, with no deaths from the disease in the former group in contrast with the worst outcome in the latter group ( P = 0.005). By multivariate analysis, pathologic tumor stage, lymph vascular invasion, and tumor ploidy were significant and independent parameters, whereas lymph node metastasis yielded no independent information. Conclusions: DNA ploidy was an independent prognostic factor in cervical carcinoma. Presence of lymph node metastasis may not always have the same impact on survival but may vary according to DNA ploidy of the primary tumor.